SARS-CoV-2 vaccine safety in adolescents with inflammatory rheumatic and musculoskeletal diseases and adults with juvenile idiopathic arthritis: data from the EULAR COVAX physician-reported registry. Issue 2 (31st July 2022) - Lawson-Tovey, Saskia; Machado, Pedro M; Strangfeld, Anja; Mateus, Elsa; Gossec, Laure; Carmona, Loreto; Raffeiner, Bernd; Bulina, Inita; Clemente, Daniel; Zepa, Julija; Rodrigues, Ana M.; Mariette, Xavier; et al.
Abstract : Background: There is a lack of data on SARS-CoV-2 vaccination safety in children and young people (CYP) with rheumatic and musculoskeletal diseases (RMDs). Current vaccination guidance is based on data from adults with RMDs or CYP without RMDs. Objectives: To describe the safety of SARS-COV-2 vaccination in adolescents with inflammatory RMDs and adults with juvenile idiopathic arthritis (JIA). Methods: We described patient characteristics, flares and adverse events (AEs) in adolescent cases under 18 with inflammatory RMDs and adult cases aged 18 or above with JIA submitted to the European Alliance of Associations for Rheumatology COVAX registry. Results: A total of 110 cases were reported to the registry. Thirty-six adolescent cases were reported from four countries, most with JIA (42%). Over half (56%) reported early reactogenic-like AEs. One mild polyarthralgia flare and one serious AE of special interest (malaise) were reported. No CYP reported SARS-CoV-2 infection postvaccination. Seventy-four adult JIA cases were reported from 11 countries. Almost two-thirds (62%) reported early reactogenic-like AEs and two flares were reported (mild polyarthralgia and moderate uveitis). No serious AEs of special interest were reported among adults with JIA. Three female patients aged 20–30 years were diagnosed with SARS-CoV-2 postvaccination; all fully recovered. Conclusions: This is an important contribution to research on SARS-CoV-2 vaccine safety in adolescents with RMDs and adults with JIA. It is important to note the low frequency of disease flares, serious AEs and SARS-CoV-2 reinfection seen in both populations, although the dataset is limited by its size.